2012
DOI: 10.1007/s00415-012-6797-7
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate interaction between open- and closed-loop postural control in phobic postural vertigo

Abstract: Phobic postural vertigo (PPV) is characterized by a subjective dizziness and postural imbalance. Changes in postural control strategy may cause the disturbed postural performance in PPV. A better understanding of the mechanisms behind this change in strategy is required to improve the diagnostic tools and therapeutic options for this prevalent disorder. Here we apply stabilogram diffusion analysis (SDA) to examine the characteristics and modes of interaction of open- and closed-loop processes that make up the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 31 publications
6
60
2
4
Order By: Relevance
“…Several investigations showed that patients with PPV manifested an alteration in postural control characterized by high frequency, low amplitude postural sway related to co-contraction of lower leg muscles when standing at rest [46,98]. One study of patients with CSD demonstrated similar results [59].…”
Section: Possible Alterations In Postural Controlmentioning
confidence: 98%
See 3 more Smart Citations
“…Several investigations showed that patients with PPV manifested an alteration in postural control characterized by high frequency, low amplitude postural sway related to co-contraction of lower leg muscles when standing at rest [46,98]. One study of patients with CSD demonstrated similar results [59].…”
Section: Possible Alterations In Postural Controlmentioning
confidence: 98%
“…In this connotation, functional is not a synonym for psychogenic or psychosomatic as it was throughout most of the 20th century and, therefore, does not reflect a presumption of psychopathological abnormalities. Studies of PPV, VV, SMD, and CSD identified a number of functional alterations in vestibular and balance mechanisms [33,37,46,59,67,68,71,88,98] associated with these clinical entities. Additional investigations separated them from primary psychiatric disorders [13,75] with which they may co-exist.…”
Section: Current Considerations For Classifying Vestibular Diseases Amentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with panic or anxiety and patients with vestibular disorders frequently present with similar avoidance behaviours and complaints including dizziness, spatial disorientation, and anxiety in particular environments [14]. Additionally, both patients with primary vestibular disorders and patients with anxiety disorders have been observed to exhibit increased visual dependence (i.e., preferential use of vision for spatial orientation and postural control) and resulting body sway [15][16][17][18].…”
Section: Introductionmentioning
confidence: 96%